The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/jhep12(2015)101
|View full text |Cite
|
Sign up to set email alerts
|

Quarkonium at finite temperature: towards realistic phenomenology from first principles

Abstract: We present the finite temperature spectra of both bottomonium and charmonium, obtained from a consistent lattice QCD based potential picture. Starting point is the complex in-medium potential extracted on full QCD lattices with dynamical u,d and s quarks, generated by the HotQCD collaboration. Using the generalized Gauss law approach, vetted in a previous study on quenched QCD, we fit Re[V ] with a single temperature dependent parameter m D , the Debye screening mass, and confirm the up to now tentative values… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
137
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 97 publications
(157 citation statements)
references
References 129 publications
(208 reference statements)
15
137
5
Order By: Relevance
“…This does not mean that in the spectral function no peak structure is visible anymore. On the contrary, when investigating S-wave quarkonium states in [1] we found that the remnant of the former bound state peak can survive to much higher temperatures after melting, according to the above criterium, has occurred. I.e.…”
Section: Jhep10(2016)032mentioning
confidence: 78%
See 4 more Smart Citations
“…This does not mean that in the spectral function no peak structure is visible anymore. On the contrary, when investigating S-wave quarkonium states in [1] we found that the remnant of the former bound state peak can survive to much higher temperatures after melting, according to the above criterium, has occurred. I.e.…”
Section: Jhep10(2016)032mentioning
confidence: 78%
“…Even though a Bayesian reconstruction is neccesary at this point, the Wilson line spectrum is much simpler than the two-body QQ spectrum itself [63] and can be robustly determined with currently available methods and simulation data sets [64]. 1 In the following we deploy the latest determination of the in-medium modification of the static complex in-medium potential from dynamical lattice QCD as in our previous S-wave study in ref. [1].…”
Section: Jhep10(2016)032mentioning
confidence: 99%
See 3 more Smart Citations